Analisis Penerapan Prinsip Keselamatan Pasien Dalam Pemberian Obat Terhadap Terjadinya Medication Error di Rawat Inap Rumah Sakit X Tahun 2018 - Tampubolon, Lediana; Pujianto, Pujianto (UI Scholars Hub, 2018)
Medication error is the incident of a drug provision that can inflicting injury to the patient with should be able to prevent as long as in control of a trained health professional, and of patients itself. From the 10 fact from World Health Organization on patient safety for the developing country in 2017 mentioned that 1 of 10 patients treated at hospital runs the risk against an onset of medical error and drug mistakes that may cause adverse effect. From the data of patient safety incident in hospital X performed from 2015 until 2016 there were 30 cases of patient safety incidents there were 12 cases of them was the case of error in administering medicine in inpatient unit. It is not conforming to standard of which are regulated by the Ministry of Health of Indonesia in 2008 which states that the incident at the hospital supposed to be zero accident. A design of this research is the qualitative study that aimed to analyze factors affecting patient safety in the process of administering medication by nurses in the X hospital for inpatient unit. The result shows that factors affecting the application of patient safety in administering medication are the lack of supervision of leaders, the lack of human resources, nursing turnover, absence of standard procedure of 7 right principle in administering medication, absence of training program for nurses, and also the lack of socialization